(untitled) (Proceedings of International Educators Conference, 2023)
In the age of digital technology there are a variety of ways to learn the language and apply it in practice. Undoubtedly, to develop speech, it is useful to work with textbooks but to enhance in communication skills teachers need to use other resources such as Internet. In addition, we can add some online platforms and apps that can combine the features and help teachers to get achievement. In this article it has been talked about the online platforms and applications as an additional and main material during the study of a foreign language and their impact on speech. This article introduces sites and services as additional material in practicing and improving English entirely as well as develop listening and reading skills.